1964
DOI: 10.1002/pol.1964.100020216
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of film formation from latices. Phenomenon of flocculation

Abstract: synopsisThe mechanism of film formation was studied with respect to the flocculation phenomenon. It was observed that almoet all latices would air-dry to a point at which coagulation of the latex particlee had juat occurred and beyond which the wet film was no longer redispersible in water. Thia flocculation point was sharp and could be detected visually or by immersing the film in water. Two methods have been devised t o measure the solids at which incipient flocculation occurred: croseeection method, and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1969
1969
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 6 publications
1
16
0
1
Order By: Relevance
“…Values higher than the theoretical value would be expected: (1) if the latex particle size distribution were bimodal, with smaller monodisperse particles of such size as to fit in the interstices between rhombohedrally packed larger monodisperse particles; (2) if the particles were deformed significantly before the polymer-polymer contacts are formed. Experimentally, Hwa [23] found that the polymer volume fraction at which the particles come into irreversible contact is about 60%, according to the stability of the latex, in agreement with the 60-64% range found for uniform macroscopic size spheres by Scott [24] and Bernal and Mason [25]. The 60-75% range found in this work is in satisfactory agreement with the foregoing values and thus is consistent with the hypothesis that the constant rate stage ends when the particles come into irreversible contact with one another.…”
Section: Resultsmentioning
confidence: 99%
“…Values higher than the theoretical value would be expected: (1) if the latex particle size distribution were bimodal, with smaller monodisperse particles of such size as to fit in the interstices between rhombohedrally packed larger monodisperse particles; (2) if the particles were deformed significantly before the polymer-polymer contacts are formed. Experimentally, Hwa [23] found that the polymer volume fraction at which the particles come into irreversible contact is about 60%, according to the stability of the latex, in agreement with the 60-64% range found for uniform macroscopic size spheres by Scott [24] and Bernal and Mason [25]. The 60-75% range found in this work is in satisfactory agreement with the foregoing values and thus is consistent with the hypothesis that the constant rate stage ends when the particles come into irreversible contact with one another.…”
Section: Resultsmentioning
confidence: 99%
“…If the latex contains surface-active compounds, the film dries with an inward-directed circular drying front, starting at the edge of the glass plate (7,47,48). This means that the measured average weight fraction as a function of time strongly differs from the weight fraction of the scanned area.…”
Section: Equipment and Measurementsmentioning
confidence: 99%
“…In 1964 Hwa (2) reported his observation that a latex cast on a flat surface first becomes optically transparent near its outer edges. He observed that during film formation, there are three regions in the plane of the film: a transparent, apparently dry region near the edges of a sample; a central turbid, wet region; and a cloudy intermediate region.…”
mentioning
confidence: 98%